A Hemi‐metallocene Chromium Catalyst with Trimethylaluminum‐Free Methylaluminoxane for the Synthesis of Disentangled Ultra‐High Molecular Weight Polyethylene. Issue 3 (11th December 2014) - Romano, Dario; Ronca, Sara; Rastogi, Sanjay
<x xml:space="preserve">Abstract</x> Recently, it has been shown that by using a single‐site catalytic system having titanium as a metallic center, it is possible to tailor the entanglement density in the amorphous region of a semi‐crystalline ultra‐high molecular weight polyethylene (UHMWPE). This route provides the possibility to make high‐modulus, high‐strength uniaxially and biaxially drawn tapes and films, without using any solvent during processing. In this publication, it is shown that a single‐site catalyst having chromium as metallic center, proposed by Enders and co‐workers, can also be tuned to provide control on the entanglement density during synthesis of the UHMWPE. However, to achieve the goal some modifications during the synthesis are required. The synthesized polymers can be processed in the solid state below the equilibrium melting temperature, resulting in uniaxially drawn tapes having tensile strength and modulus greater than 3.5 N/tex and 200 N/tex, respectively. Rheological studies have been performed to follow the increase in entanglement density in melt state with time. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>